2018
DOI: 10.1103/physrevd.98.103528
|View full text |Cite
|
Sign up to set email alerts
|

Nonadiabatic evolution of primordial perturbations and non-Gaussinity in hybrid approach of loop quantum cosmology

Abstract: While loop quantum cosmology (LQC) predicts a robust quantum bounce of the background evolution of a Friedmann-Robertson-Walker (FRW) spacetime prior to the standard slow-roll inflation, whereby the big bang singularity is resolved, there are several different quantization procedures to cosmological perturbations, for instance, the deformed algebra, dressed metric, and hybrid quantizations. This paper devotes to study the quantum bounce effects of primordial perturbations in the hybrid approach. The main discr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 116 publications
(163 reference statements)
2
37
0
Order By: Relevance
“…(Gupt and Singh, 2012;Gupt and Singh, 2013; and references therein.]. In particular, the last two approaches have been widely studied and found that they are all consistent with current cosmological observations (Agullo and Morris, 2015;de Blas and Olmedo, 2016;Castelló Gomar et al, 2017;Agullo et al, 2018;Elizaga Navascués et al, 2018;Navascues et al, 2018;Wu et al, 2018;Zhu et al, 2018). In addition, within the framework of the dressed metric approach recently it has been also shown that some anomalies from the CMB data (Akrami and Planck collaboration, 2020;Akrami and Planck collaboration, 2020;Schwarz et al, 2016) can be reconciled purely due to the quantum geometric effects (Ashtekar et al, 2020;Ashtekar et al, 2021).…”
Section: Introductionsupporting
confidence: 56%
“…(Gupt and Singh, 2012;Gupt and Singh, 2013; and references therein.]. In particular, the last two approaches have been widely studied and found that they are all consistent with current cosmological observations (Agullo and Morris, 2015;de Blas and Olmedo, 2016;Castelló Gomar et al, 2017;Agullo et al, 2018;Elizaga Navascués et al, 2018;Navascues et al, 2018;Wu et al, 2018;Zhu et al, 2018). In addition, within the framework of the dressed metric approach recently it has been also shown that some anomalies from the CMB data (Akrami and Planck collaboration, 2020;Akrami and Planck collaboration, 2020;Schwarz et al, 2016) can be reconciled purely due to the quantum geometric effects (Ashtekar et al, 2020;Ashtekar et al, 2021).…”
Section: Introductionsupporting
confidence: 56%
“…Finally, we note that the linear perturbations of mLQCs were recently studied numerically in [25]. It would be very interesting to study the same problem analytically along the lines presented in [28,29,[58][59][60], by using the analytical solutions obtained in our analysis along with the method recently developed in [61][62][63]. This exercise will be performed in a future publication.…”
Section: Discussionmentioning
confidence: 90%
“…Now LQC is in a position to undergo experimental tests and to look for observational signature of quantum bounce, pre-inflationary dynamics in current/forth-coming observations. In fact three major streams of calculations of cosmological perturbations, namely, dressed metric, deformed algebra and hybrid approaches [44], [50], [51] have been carried out and studied numerically and analytically in [52], [53], [54], [55], [56]. It has been reported that the deformed algebra approach is already inconsistent with current observations [57].…”
Section: Introductionmentioning
confidence: 99%